RPV Integrity and Fracture Mechanics 2004
DOI: 10.1115/pvp2004-2728
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Flaw Assessment Methods in the RSE-M Code

Abstract: The RSE-M Code provides rules and requirements for inservice inspection of French Pressurized Water Reactor power plant components. Appendices 5.3 and 5.4 of the Code give non mandatory guidance for analytical evaluation of flaws, i.e. fracture mechanics analyses based on simplified methods. Flaw assessment aims to calculate the initiation and the subsequent propagation of the crack under cyclic loading (fatigue analysis) and then to assess the crack stability, by comparing the applied J integral to the toughn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…This is at the lower end of being consistent with our z = 3 measurements, and should the same escape fraction hold at z = 0.3, would also be consistent with our estimates in the nearby universe. However, the Le Delliou et al (2005) escape fraction is highly inconsistent with our estimates at higher redshift. These semi-analytical models, using the prescription of Baugh et al (2005), categorized star-formation as occurring in two discrete modes, with a normal Salpeter IMF (α = −1.35) assigned to quiescent star-formation and a flat IMF (α = 0) for bursting systems.…”
Section: Comparison With the Literaturecontrasting
confidence: 99%
See 1 more Smart Citation
“…This is at the lower end of being consistent with our z = 3 measurements, and should the same escape fraction hold at z = 0.3, would also be consistent with our estimates in the nearby universe. However, the Le Delliou et al (2005) escape fraction is highly inconsistent with our estimates at higher redshift. These semi-analytical models, using the prescription of Baugh et al (2005), categorized star-formation as occurring in two discrete modes, with a normal Salpeter IMF (α = −1.35) assigned to quiescent star-formation and a flat IMF (α = 0) for bursting systems.…”
Section: Comparison With the Literaturecontrasting
confidence: 99%
“…Adopting a similar method of LF scaling by luminosity, Le Delliou et al (2005) found that an escape fraction of 2 % was sufficient to match observed Lyα LFs with their predictions based upon semi-analytical models between z = 2 and 6, with the same machinery able to predict the clustering properties of Lyα emitters (Orsi et al 2008). This is at the lower end of being consistent with our z = 3 measurements, and should the same escape fraction hold at z = 0.3, would also be consistent with our estimates in the nearby universe.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Since the interaction between dark energy and dark matter modifies the growth rate of the density perturbation of dark matter compared with baryon which is not expected to have direct interaction with dark energy, the overdensity of dark matter and baryon collapse with different rate in coupled dark energy models. As a result, the ratio of baryon density to dark matter density in the clusters is influenced by the interaction between dark energy and dark matter [58,59]. However, to avoid the complexities of the collapsing processes, we do not consider this influence and ignore baryon in our consideration similar to the analysis in [27,53].…”
Section: Evolution Equationsmentioning
confidence: 99%
“…prior to processing of the line through the IGM) is the same at z = 6.5 as at z = 5.7. More realistic models, based on the hierarchical growth of structures, combined with Lyman α line processing by gas and dust interior to the galaxies, predict that the number of emitters were smaller at earlier epochs (Haiman and Spaans 1999; Le Delliou et al 2004), which would strengthen the limits on x HI below.…”
Section: An Upper Limit From the Abundance Of Lyman α Emittersmentioning
confidence: 99%